Brand Equity Valuation Through Big Data Intelligence - Steffen Schmidt; Frank Buckler; Sascha Langner; Klaus-Peter Wiedmann (Marketing Review St.Gallen, 2016)
The internet provides the informative potential for brand companies to display an actual brand report. The present work introduces and examines a systematic brand equity valuation based on an advanced and intelligent data analysis applied to data extracted from the internet. Specifically, the developed model approach convinces with a high predictive power.
Keywords: 650